2009
DOI: 10.1016/j.jqsrt.2009.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Circular polarization in scattered light as a possible biomarker

Abstract: Original article can be found at : http://www.sciencedirect.com/ Copyright ElsevierBiological molecules exhibit homochirality and are optically active. Therefore, it is possible that the scattering of light by biological molecules might result in a macroscopic signature in the form of circular polarization. If this is the case, then circular polarization spectroscopy, which may be utilized in remote sensing, can offer a powerful indicator of the presence of a universal biosignature, namely homochirality. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…Homochirality should be detectable via circular polarisation (Sparks et al 19 ), but the signal from a planet covered with primitive life is likely (at least) an order of magnitude smaller than the degree of linear polarisation from atmospheric scattering. Even larger telescopes (with a very good control of polarization cross-talk) will therefore be required to answer the biggest question of all: 'Is there other life out there?'…”
Section: Searching For Biomarkers With Spectroscopymentioning
confidence: 99%
“…Homochirality should be detectable via circular polarisation (Sparks et al 19 ), but the signal from a planet covered with primitive life is likely (at least) an order of magnitude smaller than the degree of linear polarisation from atmospheric scattering. Even larger telescopes (with a very good control of polarization cross-talk) will therefore be required to answer the biggest question of all: 'Is there other life out there?'…”
Section: Searching For Biomarkers With Spectroscopymentioning
confidence: 99%
“…Early studies of Pospergelis (1969) followed by Wolstencroft (1974) and others presented measurements of full Stokes and circular polarization of leaves and mineral samples. Sparks et al (2009) continued this investigation with microbes. It was found that a unique circular polarization signature associated with homohirality in living organisms is extremely weak (5 × 10 -4 at most under laboratory conditions) which would require unrealistic exposure time with a gigantic space telescope to be detected on distant planets, but it can perhaps be searched for in the Solar system objects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all known biological systems have evolved to prefer a particular chirality (or handedness) of organic molecules. This asymmetry in the occurrence of stereoisomers can lead to a unique polarization signal through circular dichroism or optical activity [7,10]. In order to exploit these phenomena one needs to build a polarimeter that can measure both linear and circular polarization, using a robust design that is suitable for a moving platform.…”
mentioning
confidence: 99%
“…However, polarization has not been as extensively investigated for imaging applications, although some exciting applications are starting to be explored. [6], and the search for biological activity on other planets [7]. There are even some animals, such as the mantis shrimp, that have evolved sophisticated polarimetric visual systems to obtain valuable information from their environment, and are sensitive to all the polarization components of light [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation